Carbon Emission Disclosure: The Influence of External Stakeholder Preassure and Environment Performance - Nur Prasetyo Aji; Fatimah Aulia Rahman; Laila Oshiana Fitria A’zizah; Mega Wahyu Widawati (Lafadz Jaya Publisher, 2023)
The purpose of this paper is to investigate the effect that pressure from external stakeholders and environmental performance have on the reporting of carbon emissions by corporations. Purposive sampling was utilized to pick samples for use in this study. These samples were selected from sustainability reports and annual reports of companies that were registered with the Asia Sustainability Reporting Rating (ASRRAT) for 2019–2021. The data that was used in this study was considered to be secondary data. This investigation takes a quantitative approach and using a method called Multiple Regression Analysis. According to the study's findings, institutional ownership, diffusion ownership, and environmental performance have no discernible influence on the disclosure of carbon emissions, whereas the media exposure variable significantly affects the degree of disclosure.